2005
DOI: 10.1002/pbc.20308
|View full text |Cite
|
Sign up to set email alerts
|

Differential mRNA expression of glucocorticoid receptor α and β is associated with glucocorticoid sensitivity of acute lymphoblastic leukemia in children

Abstract: The amounts of GR isoform mRNA in leukemic blasts were closely correlated with sensitivity to glucocorticoid exposure. The mRNA expression pattern of GR isoforms at initial presentation may provide valuable information for prognosis in children with newly diagnosed ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…GRh has been reported to suppress transactivation of GRa by synthetic glucocorticoids, and high levels of GRh may correlate with insensitivity to glucocorticoid-induced apoptosis (33,34). We therefore examined GRh regulation by PDE4 inhibitors in B-CLL.…”
Section: Resultsmentioning
confidence: 99%
“…GRh has been reported to suppress transactivation of GRa by synthetic glucocorticoids, and high levels of GRh may correlate with insensitivity to glucocorticoid-induced apoptosis (33,34). We therefore examined GRh regulation by PDE4 inhibitors in B-CLL.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the GR␤ isoform can inhibit glucocorticoid signaling in a dominant-negative fashion by heterodimerization with GR␣ (33,34). Increased GR␤ production has been associated with glucocorticoid resistance in immune system diseases including asthma and acute lymphoblastic leukemia (35,36). Interestingly, the rs6198 A/G polymorphism that shows strong associations with BP traits in EA is located in exon 9␤, disrupting a consensus sequence element in the 3Ј UTR that is known to destabilize mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…GRβ levels are also elevated in glucocorticoid-resistant cases of asthma [51], rheumatoid arthritis [52], ulcerative colitis [53], and systemic lupus erythematosus [54]. High GRβ expression is also associated with glucocorticoid resistance in acute lymphoblastic leukemia and chronic lymphocytic leukemia [55, 56]. Manipulating GRα/GRβ expression ratios, therefore, may provide a means to modulate glucocorticoid sensitivity.…”
Section: The Glucocorticoid Receptormentioning
confidence: 99%